Pengaruh Pemahaman Wajib Pajak Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di Kota Jambi - Anugerah, Muhammad Alfa; Iqbal, Johandri; Adinda, Pramesti Nurul (Journal of Applied Accounting And Business, 2024)
The purpose of this research is to determine the effect of taxpayer understanding on individual taxpayer compliance, to determine the effect of tax sanctions on individual taxpayer compliance, to determine the effect of taxpayer understanding and tax sanctions on individual taxpayer compliance in the city of Jambi. The population used in this research is individual taxpayers in the city of Jambi. The population used in this research in 2022 will be 230,533. Sampling uses the probability sampling method. The sample in this study was 100 individual taxpayers. The data collection technique is questionnaire media. The data analysis techniques used are data validity and reliability, multiple linear regression, classical assumptions, coefficient of determination and hypothesis using the t test and F test. The results of this research show that understanding taxpayers influences individual taxpayer compliance. Tax sanctions affect individual taxpayer compliance. Taxpayer understanding and tax sanctions jointly influence individual taxpayer compliance